Combined Resistance and Plyometric Training Is More Effective Than Plyometric Training Alone for Improving Physical Fitness of Pubertal Soccer Players - Zghal, Firas; Colson, Serge S.; Blain, Grégory; Behm, David G.; Granacher, Urs; Chaouachi, Anis (Frontiers in Physiology, 2019)
The purpose of this study was to compare the effects of combined resistance and plyometric/sprint training with plyometric/sprint training or typical soccer training alone on muscle strength and power, speed, change-of-direction ability in young soccer players. Thirty-one young (14.5 ± 0.52 years; Tanner stage 3-5) soccer players were randomly assigned to either a combined- (COMB, n=14), plyometric-training (PLYO, n=9) or an active control group (CONT, n=8). Two training sessions were added to the regular soccer training consisting of one session of light-load high-velocity resistance exercises combined with one session of plyometric/sprint training (COMB), two sessions of plyometric/sprint training (PLYO) or two soccer training sessions (CONT). Training volume was similar between the experimental groups. Before and after 7-weeks of training, peak torque, as well as absolute and relative (normalized to torque; RTDr) rate of torque development (RTD) during maximal voluntary isometric contraction of the knee extensors (KE) were monitored at time intervals from the onset of contraction to 250 ms. Jump height, sprinting speed at 5, 10, 20-m and change-of-direction ability performances were also assessed. There were no significant between–group baseline differences. Both COMB and PLYO significantly increased their jump height (∆14.3%; ES=0.94; ∆12.1%; ES=0.54 respectively) and RTD at mid to late phases but with greater within effect sizes in COMB in comparison with PLYO. However, significant increases in peak torque (∆16.9%; p<0.001; ES=0.58), RTD (∆44.3%; ES=0.71), RTDr (∆27.3%; ES=0.62) at early phases and sprint performance at 5-m (∆-4.7%; p<0.001; ES=0.73) were found in COMB without any significant pre-to-post change in PLYO and CONT groups. Our results suggest that COMB is more effective than PLYO or CONT for enhancing strength, sprint and jump performances.